2013
DOI: 10.1186/1471-2334-13-442
|View full text |Cite
|
Sign up to set email alerts
|

High clustering rates of multidrug-resistant Mycobacterium tuberculosisgenotypes in Panama

Abstract: BackgroundTuberculosis continues to be one of the leading causes of death worldwide and in the American region. Although multidrug-resistant tuberculosis (MDR-TB) remains a threat to TB control in Panama, few studies have focused in typing MDR-TB strains. The aim of our study was to characterize MDR Mycobacterium tuberculosis clinical isolates using PCR-based genetic markers.MethodsFrom 2002 to 2004, a total of 231 Mycobacterium tuberculosis isolates from TB cases country-wide were screened for antibiotic resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 24 publications
(22 reference statements)
0
13
0
Order By: Relevance
“…Due to its key location at the isthmus between North and South America, Panama has undergone great demographic and population changes of diverse geographic origins, which has probably affected the composition of circulating MTB strains. Few and discontinuous efforts have been made to genotypically characterize MTB isolates, mainly on convenience samples (Rosas et al, 2013;Sambrano et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Due to its key location at the isthmus between North and South America, Panama has undergone great demographic and population changes of diverse geographic origins, which has probably affected the composition of circulating MTB strains. Few and discontinuous efforts have been made to genotypically characterize MTB isolates, mainly on convenience samples (Rosas et al, 2013;Sambrano et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…To characterize the Mycobacterium-like organisms, samples of granulomas from liver, spleen, lymph node, hilum and intestine were submitted for molecular identification. Enzymatic DNA extraction using lysozymes was performed according to the protocol described by Rosas et al [18]. Molecular identification was based on PCR-restriction fragment length polymorphism analysis (PRA) of the hsp65 as previously described [22,23].…”
Section: Casementioning
confidence: 99%
“…Although it began as a relatively insignificant disease during the 1980s, HIV prevalence has since escalated to become one of the leading, global causes of morbidity and mortality [2,3]. For example, the World Health Organization [4] reported that by the end of 2015 there were 36.9 million HIV-positive individuals globally, while 1.2 million deaths occurred as a result of HIV-related causes.…”
Section: Introductionmentioning
confidence: 99%